Carbon Ion Irradiation Enhances the Anti-tumor Efficiency in Tongue Squamous Cell Carcinoma via Modulating the FAK Signaling - Si, Qingzong; Ye, Qian; Bing, Zhitong; Fan, Ruihong; Hu, Xiaoli; Liu, Bin; Wang, Jizeng; Liu, Yang; An, Xiaoli (Frontiers in Public Health, 2021)
Oral cancer is a very aggressive disease with high rates of recurrence and metastasis. This study aimed at addressing how efficiently tongue cancer is suppressed after carbon ion irradiation. Here, the close relationship between upregulated expression of focal adhesion kinase (FAK) and high metastatic status in tongue squamous cell carcinoma patients was validated using bioinformatics and immunohistochemical analyses. Our data indicated that FAK suppression significantly enhanced the killing effect induced by irradiation in the tongue cancer cell line CAL27, as evidenced by increased apoptotic induction and reduced colony formation. More importantly, in FAK-deficient cells, carbon ion irradiation was shown to remarkably inhibit migration and invasion by delaying wound healing and slowing down motility. Further studies revealed that irradiation exposure caused disorganization of the actin cytoskeleton and reduced cell adhesive energy in FAK-deficient cells. Moreover, carbon ion treatment, in combination with FAK silencing, markedly blocked the phosphorylation levels of FAK, and paxillin, which partly contributed to the reduced motility of tongue squamous cell carcinoma CAL27 cells. Collectively, these results suggest that the prominent obstructing role of carbon ion irradiation in the growth inhibition and metastatic behavior of tumors, including attenuation of cell adhesiveness, motility, and invasiveness, could be distinctly modulated by FAK-mediated downstream pathways.